Prussian Blue Modified Solid Carbon Nanorod Whisker Paste Composite Electrodes: Evaluation towards the Electroanalytical Sensing of H2O2. (12th March 2012) - Siimenson, Carolin; Kruusma, Jaanus; Anderson, Erik; Merisalu, Maido; Sammelselg, Väino; Lust, Enn; Banks, Craig E.
Abstract : Metallic impurity free solid carbon nanorod "Whiskers" (SCNR Whiskers), a derivative of carbon nanotubes, are explored in the fabrication of a Prussian Blue composite electrode and critically evaluated towards the mediated electroanalytical sensing of H2 O2 . The sensitivity and detection limits for H2 O2 on the paste electrodes containing 20% (w/w) Prussian Blue, mineral oil, and carbon nanorod whiskers were explored and found to be 120 mA/(M cm 2 ) and 4.1 μM, respectively, over the concentration range 0.01 to 0.10 mM. Charge transfer constant for the 20% Prussian Blue containing SCNR Whiskers paste electrode was calculated, for the reduction of Prussian Blue to Prussian White, to reveal a value of 1.8 ± 0.2  1/s (α = 0.43, N = 3 ). Surprisingly, our studies indicate that these metallic impurity-free SCNR Whiskers, in this configuration, behave electrochemically similar to that of an electrode constructed from graphite.